Is tocilizumab a potential therapeutic option for refractory unicentric Castleman disease?. Issue 1 (11th April 2017) - Abid, Muhammad Bilal; Peck, Rachel; Abid, Muhammad Abbas; Al‐Sakkaf, Wesam; Zhang, Yuening; Dunnill, Giles S.; Staines, Konrad; Sequeiros, Iara‐Maria; Lowry, Lisa
Abstract: Castleman disease is a rare lymphoproliferative disorder with 2 distinctly defined clinical forms. While multicentric Castleman disease (UCD) poses a potential therapeutic challenge, unicentric variant has historically been considered curable with surgical resection. Hence, little is known to guide management of patients with UCD, refractory to surgical resection and combination chemotherapy. We present a case of a patient, negative for HIV and HHV‐8, who had an unsuccessful surgical intervention and no response to radiotherapy and chemotherapy. He had severe paraneoplastic pemphigus and was treated with tocilizumab, an anti‐interleukin‐6 receptor monoclonal antibody that has demonstrated good response rates in multicentric Castleman disease but demonstrated no clinical response despite 2 months of treatment. Our report is the first to describe a lack of response to tocilizumab in the rare setting of refractory UCD and discuss potential for distinct disease biology.